Family functions to increase breastfeeding self efficacy of adolescent primigravida - Hidayati, Ratna; Huda, Moch. Maftuchul; Setyorini, Dhiana; Astutik, Wahyu Sri (International Journal of Public Health Science (IJPHS), 2024)
Primigravida in adolescence will experience changes in situations that require the ability to adapt to pregnancy, thereby affecting their confidence in breastfeeding their babies. The function of the family is to help prepare the pregnant mother's needs to face the changes of pregnancy, prepare for childbirth and overcome difficulties in breastfeeding. This research aims to determine the function of the family in increasing breastfeeding self-efficacy of adolescent primigravida. Correlational research design, population and sample of 124 teenage primigravida respondents using total sampling technique. The independent variable family function was measured using the family assessment device (FAD) questionnaire and the dependent variable breastfeeding self-efficacy using the breastfeeding self-efficacy scale short form (BSES-SF) questionnaire which was analyzed using the Rho Spearman rank test. The research results showed that almost all respondents (90.3%) had healthy family functions and almost all respondents (83.9%) had high self-confidence. The statistical test results showed a significant p-value of 0.000 (α<0.05) with r=0.746. The function of the family in providing a sense of security and comfort creates a positive attitude among adolescent primigravida towards breastfeeding self-efficacy. Breastfeeding self-efficacy needs to increase breastfeeding success and prevent stunting.